The Multiple Voices of the United Nations on the Venezuelan and Nicaraguan Crises: A Sociological Approach of International Organizations. (20th May 2020) - Brun, Élodie; Parthenay, Kevin
Abstract : Various United Nations organizations and representatives have released declarations about the deterioration of the Venezuelan and Nicaraguan situations since 2017. The United Nations Security Council, the General‐Secretary, and the Office of the High Commissioner for Human Rights have been particularly active on these issues. The positions of the selected institutions and their representatives were diverse, and sometimes contradictory, and the polarized contexts in which such declarations have been made emphasized diversity. Based on a sociological approach of international organizations, this article demonstrates that the United Nations as an actor is not a coherent and unique entity. To understand the difficulties the organization faces in dealing with the Venezuelan and Nicaraguan crises, it seems indispensable to go beyond the traditional dichotomy between states and institutions, and power politics. Indeed, institutions are plural—the United Nations through states is conservative and cautious, whereas the United Nations through the individuals and staff is more assertive and critical of the Venezuelan and Nicaraguan governments. Abstract : Varios organismos y representantes de las Naciones Unidas han publicado declaraciones sobre el deterioro de las situaciones en Venezuela y Nicaragua desde 2017. En particular, el Consejo de Seguridad de las Naciones Unidas, el Secretario General y la Oficina del Alto Comisionado para los Derechos Humanos han sido muy activos en estas cuestiones. Las posiciones de estas instituciones y sus representantes fueron diversas, a veces contradictorias, y los contextos polarizados en los cuales se inscriben agudizaron esta diversidad. Basado en la perspectiva sociológica de las organizaciones internacionales, este trabajo demuestra que las Naciones Unidas como actor no es una entidad coherente y monolítica. Para entender las dificultades encontradas por la organización a la hora de lidiar con las crisis en Venezuela y Nicaragua, es necesario rebasar la dicotomía tradicional entre estados e instituciones, y la política del poder. En efecto, las instituciones son plurales a la hora de posicionarse sobre las decisiones de los gobiernos venezolano y nicaragüense—la ONU es conservadora y prudente a través de los estados, mientras que es más crítica y perentoria a través de los individuos y los funcionarios. Abstract : 2017年以来，联合国不同组织及代表都发布了有关委内瑞拉和尼加拉瓜形势恶化的宣言。联合国安理会、联合国秘书长、以及联合国人权事务高级专员办事处在这类问题上尤为活跃。被指派的机构及其代表所持的立场多样化，且有时相互抵触，同时这类宣言是在强调多样性的极化背景下产生的。基于国际组织的一项社会学方法，本文证明，联合国作为行动方并没有将自身展现为一个连贯且独特的实体。为理解机构在应对委内瑞拉和尼加拉瓜危机时面临的困境，似乎必须要不局限于国家和机构之间传统的二分法，以及权力政治。机构确实是多元的：通过国家进行联合国行动是保守和谨慎的，但通过个人和员工进行联合国行动则能更为自信和批判地看待委内瑞拉和尼加拉瓜政府。